Enrichment in procoagulant microparticles in calcified human aortic valve – role in valvular endothelium alterations and enhanced thrombogenicity. (3rd October 2022) - Hmadeh, S; Trimaille, A; Matsushita, K; Zobairi, F; Sato, C; Kindo, M; Hoang, T; Marchandot, B; Toti, F; Zibara, K; Hamade, E; Schini Kerth, V; et al.
Abstract: Background: Aortic stenosis (AS) is characterized by endothelial dysfunction (ED), inflammatory cell infiltration, myofibroblastic and osteoblastic differentiation. Subclinical leaflet thrombosis was recently linked to higher rates of stroke and transient ischemic attack after transcatheter aortic valve implantation (TAVI). Procoagulant microparticles (MPs) are associated with ED, inflammation and clot formation. There is limited evidence regarding intra-valvular MPs content and their potential biological effects. This question is particularly relevant in TAVI in which the residing native valve could constitute a source of thrombotic activity enhancing leaflet thrombosis and valve dysfunction. Purpose: Therefore, we hypothesized that MPs trapped within the native aortic valve contribute to valvular dysfunction including enhanced thrombogenicity. Methods: Human valves were collected from patients undergoing surgical valve replacement for AS or aortic insufficiency (AI). Pro-thrombotic, pro-inflammatory, and ED markers were identified in the calcified vs non-calcified part of the valves by Western-blot. Calcium content was measured through colorimetric method. MPs were extracted from human pathological valves, and quantified through their prothrombinase activity. Primary cultures of porcine valvular endothelial cells (VEC) were treated with the MPs (10 nmol/L) or thrombin (1U/ml) for 24hrs. Phenotypic change was appreciated through gene expression pattern assessed by RT-qPCR. IL-8 secretion was measured by ELISA. Results: The phenotype of the AS valve was characterized through increased expression of thrombogenic (tissue factor, thrombomodulin, PAI-1), adhesive (VCAM-1, ICAM-1) and inflammatory (COX-1, COX-2) molecules in the calcified part of the valve. Moreover, MPs content was increased in the calcified vs non-calcified part of the valve or AI valves. MPs levels was correlated with valvular calcium content (R=0.3862: p<0.001). Tissue factor was increased in MPs extracted from AS vs AI. The biological effect of MPs was tested on VEC in-vitro. Results showed dramatic increase in expression of inflammatory cytokines (CXCL10, CCL11, CXCL8, MCP1) adhesion molecules (VCAM-1, ICAM-1, SELP, SELE) and proangiogenic factors (VEGFR2, ANGPTL4) in VEC exposed to MPs (24h) from AS vs AI. Enhanced secretory phenotype was evidenced through IL-8 determination in the supernatant of VEC stimulated with MPs from AS valve. Conclusion: Calcified aortic valve is a potent reservoir of MPs, acting as a pro-thrombogenic source per se and promoting a switch of VEC phenotype toward prothrombotic, proinflammatory and proangiogenic pattern. These data suggest that MPs released from the native valve constitute an important source of mediators involved in enhanced thrombogenicity and valvular remodeling. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): GERCA-Groupe Etudes Reali Commercia Avignon